Effect of shape and size of carbon materials on the thermophysical properties of magnesium nitrate hexahydrate for solar thermal energy storage applications. (September 2021) - Gupta, Neeraj; Kumar, Amit; Dhasmana, Hrishikesh; Kumar, Avshish; Verma, Abhishek; Shukla, Prashant; Jain, V.K.
Highlights: Various carbon materials were used as fillers in magnesium nitrate hexahydrate matrix (MNH). MNH-carbon composites were prepared by a simple melt mixing technique. The optimum concentration of fillers was 0.5 wt.% to exploit best thermophysical properties. The MNH-carbon sphere composite exhibit 100% enhancement in thermal conductivity and show least degree of supercooling. Prepared MNH-carbon sphere composite can be used as active material in Instant solar water heating systems. Abstract: In this paper, the effect of various carbon materials having different shapes and sizes on the thermophysical properties of magnesium nitrate hexahydrate (MNH), salt hydrate is studied. The carbon materials such as carbon sphere, multi-walled carbon nanotubes (MWCNTs), mesoporous carbon, graphene nanoplatelets(GNPs), and nano graphite (NG) were used as filler independently in the matrix of MNH to prepare MNH-carbon composite by melt mixing technique. The scanning electron microscopy (SEM) and Energy-dispersive X-ray Spectroscopy (EDX) analysis were done to analyze the uniform dispersion of carbon materials in MNH matrix. Fourier transformed infrared (FTIR) analysis was done to investigate the interaction between carbon materials and MNH in MNH-carbon composites. The cyclic stability of developed composites was verified by thermogravimetric analysis. The thermal conductivity of MNH enhanced significantly by 100%, 82.5%, 75%, 72.5%, and 65% upon adding carbon sphere, MWCNTs, mesoporous carbon, GNPs, and NG respectively, at a mass fraction of 0.5 wt.%. Differential scanning calorimetry results reveal that the addition of carbon materials improves the phase change properties of composites without compromising on the latent heat capacity of the material and also reduces the supercooling effect. To investigate the practical viability of prepared MNH-carbon composites, the heat transfer characteristics were evaluated by a conventional heating system. The maximum reduction in charging time was observed in the case of MNH-carbon sphere composite. Finally, the best MNH-carbon composite having highest thermal conductivity and stability, least supercooling, was used as active material in an indigenously built instant solar water heating system for solar thermal energy storage applications. Graphical abstract: Image, graphical abstract